Comparison of hydrogen permeation and structural properties of a microporous silica membrane and a dense BaCe0.9Y0.1O3-δ (BCY) perovskite membrane - Mahdi Amanipour; Marzieh Heidari; Martin Walberg (Results in Materials, 2022)
Silica composite membranes and BaCe0.9Y0.1O3-δ (BCY) perovskite membranes were successfully synthesized to separate hydrogen in an equimolar mixture of H2, CH4, CO, and CO2 at temperature range of 500–900 °C and pressure difference of 1 bar. The phase structure of both membranes was characterized by X-ray diffraction (XRD). Thermogravimetric analysis (TGA) was used to evaluate phase stability of perovskite membrane. FESEM images confirmed graded structure of silica membrane and uniform, dense structure of perovskite membrane. H2 permeation in semi-dense silica layer deposited on alumina substrate indicated that permeation in top selective layer follows a diffusion mechanism which is based on jumps between solubility sites. On the other hand, low permeation rates of around 10−8 mol m−2 s−1 Pa−1 in perovskite membranes revealed a proton-electron conductivity mechanism which occurs through dense structures. Increasing hydrogen separation factor (SF) in gas mixture by increasing deposition time from 3.5 h to 6 h in silica composite membrane confirms formation of crack-free selective layer; however, this factor is still lower than SF of 0.97–0.99 in perovskite membranes. A set of gas-permeability data is collected at the laboratory scale for the statistical characterization of both membrane types (P01, S01) to provide a dataset from which one can assess statistical scaling features displayed by the data and their scaling increments.